A Familial Heterozygous Null Mutation of MET in Autism Spectrum Disorder2. Issue 5 (6th June 2014) - Lambert, Nelle; Wermenbol, Vanessa; Pichon, Bruno; Acosta, Sandra; van den Ameele, Jelle; Perazzolo, Camille; Messina, Diana; Musumeci, Maria‐Franca; Dessars, Barbara; De Leener, Anne; Abramowicz, Marc; Vilain, Catheline
<x xml:space="preserve">Abstract</x> Autism spectrum disorder (ASD) results from interactions of genetic and environmental factors. The MET proto‐oncogene has been identified as a candidate gene for autism susceptibility, and is implicated in neurodevelopment and social brain circuitry. Here, we describe the first case of a familial mutation of MET, consisting of an interstitial genomic deletion removing exons 12 through 15, causing a frameshift and premature stop codon, with evidence of nonsense‐mediated mRNA decay. On the other allele, patients carried the C allele of the MET promoter rs1858830 polymorphism, known to decrease MET expression and previously associated with autism susceptibility. The heterozygous mutation was associated with autism in one patient, and language and social impairment in a sibling. Our observations delineate the phenotypic spectrum associated with a clearly defined, very likely complete loss of function mutation of MET. Incomplete penetrance in this family was consistent with MET as a partial susceptibility gene for ASD. Implication of MET in normal and pathological brain development opens new perspectives for understanding the pathophysiology of autism and for eventual therapeutical clues. Autism Res2014, 7: 617–622. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.